(untitled) (Applied Biological Research, 2023)
The natural resources and agriculture ecosystem are adversely damaged due to the fast buildup of toxic pollutants such as radionuclide, organic contaminants and heavy metals emitted from industries and other anthropogenic activities. A polyhouse experiment was conducted to assess the capability of fennel (Foeniculum vulgare) to remediate a metal contaminated soil, collected from Moradabad (a hub of electroplating industries), by the application of different levels of cow manure. Metal analysis of root and aerial parts was performed using AAS and essential oil composition by GC and GC/MS. The results revealed that the use of cow manure at 52 t ha-1 gave highest plant growth and oil yield. Limonene, trans-anethole and dillapiole were the major constituents among all the amendments. The highest content of trans-anethole (56.05%) was noticed at 52 t ha-1. The addition of cow manure reduced Zn, Ni, Cu and Cr concentration in plant tissues. Maximum reduction was found at 104 t ha-1. Cr showed highest BCF at 0 t ha-1, while Cu showed lowest BCF at 104 t ha-1. Therefore, cow manure use in the metal contaminated soils had favourable impact on the growth characters and essential oil composition of fennel.